Triple Bottom Line, Sustainability, and Regional Development - Darko B. Vukovic; Vladislav Spitsin; Elena Akerman; Irina Gammerschmidt (Journal of Eurasian Studies)
In a study of 74 Russian regions over the period of 2013–2018, this paper demonstrates that economic, social, and ecological dimensions of the triple bottom line triad positively and significantly affect regional development, thus validating the growing emphasis on sustainable development found in the literature and among policymakers. Investments in research and development, the creation of new firms, reductions in poverty rates, and lowering emission intensity lead to regional development. The study develops four models to analyze the regional resource allocation efficiency in relation to the economic, social, and ecological goals of sustainable development. To assess regional development, this paper calculates the technical efficiency of the regions concerning technological frontiers using Data Envelopment Analysis (DEA). As one of our variables (the border region dummy) is time-invariant, the study chose to estimate models with the help of a random effects estimator. The effects of startup rates and ecological factors are moderated by the per capita income within the region. The results suggest that the triple bottom line agenda is justified as a regional development paradigm.